Asymmetries in the reading competence of English and Spanish speakers in dual immersion programs: A quantitative and cross-sectional study - Capdevila-Gutierrez, Maria; Moya-Guijarro, A. Jesus (Education Policy Analysis Archives, 2022)
Dual immersion programs (also known as two-way immersion or TWI), which ideally combine students of two linguistic groups, 50% of speakers of the target language and 50% of the majority language, have been proven effective in the achievement of similar levels of biliteracy and academic success in both languages. They also guarantee the closing of the achievement gap between the two groups. Nonetheless, it seems that similar levels of biliteracy are not always present in all students by the end of the program life. This asymmetry can affect both the level of biliterate proficiency and the academic achievement. The present quantitative, cross-sectional study was carried on in a secondary dual immersion program implemented in a school district in Southern California. The study compares the achievement in all four skills of Spanish language, especially in reading comprehension, of two groups of students (Spanish and English speakers), over a four-year span. Using the scores from a standardized language test in Spanish (DELE Escolar), we analyze and compare results to confirm or reject the hypothesis that scores reflecting literacy through reading comprehension are, on average, better in one group of students than in the other. We also delve into the reasons for this potential mismatch and revise the educational practices and policies that may be causing this deficiency in the outcome of these enrichment programs.